Configuration Design of Novel Manually Operated Dynamo Flashlights - WANG, Hsin-Te; YAN, Hong-Sen (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2007)
This paper synthesizes novel configurations of manually operated dynamo flashlights. Topology and motion characteristics of existing gear dynamos are modified and concluded. The structural sketches and corresponding graph representations for gear trains and dynamos with the defined induced magnetic circuits are defined. Through the concepts of generalization and specialization, the atlas of the structural sketches and graphs of the embedded gear dynamos is obtained subject to the defined design requirements and constraints. And, a systematic approach is proposed to synthesize the novel mechanisms of the embedded gear dynamos. As a result, the embedded three-link and four-link gear dynamos have 12 and 24 novel design configurations, respectively. One prototype of the embedded three-link and another of the embedded four-link gear dynamo are built.